Investigations on fatigue curves in dependency of water quality for nickel-martensitic steels. Issue 1 (June 2021) - Leibing, B; von Locquenghien, F; Rückle, D; Schellenberg, G
Abstract: With the need for flexible operation, Francis runners are exposed to various operating conditions outside the traditional operating range. To grant sufficient fatigue life, a deep knowledge of both loads and material behavior is mandatory. With the change in operation diverse stress amplitudes and number of cycles have to be considered for the comparison with fatigue curves. Hydro power turbines are exposed to possible corrosion attack due to the surrounding water environment, which is a relevant impact on the fatigue curves. Therefore an overview of parameters that influence the corrosivity will be given. From an evaluation of a database that contains water quality data of worldwide hydro power projects, different water qualities are defined to perform fatigue tests with the influence of a corrosive medium. For selected water qualities, preliminary material test results will be presented.